RULE OF LAW AND ELECTRONIC LEGAL PROCEDURE: ANALYSIS OF THE RELATIONSHIP - Николина , Катерина (Київський національний університет імені Тараса Шевченка, 2022)
The purpose of this article is to establish the compliance of electronic procedures with the requirements of the rule of law, which is currently the main criterion for the legitimacy of the activities of state authorities. The methodological basis of the scientific work was made up of general scientific and special-legal methods, in particular systemic, analysis and synthesis, formal and legal, and comparative-legal. The author clarified the main approaches to understanding the category of legal procedure, proposed classification criteria depending on the presence of a connection with the legal process into procedural and non-procedural ones. The article examines the peculiarities of improving procedures in the field of law enforcement, particularly judicial proceedings, under the influence of digital transformation. The author formulated the concept of electronic legal procedure as a special type of legal procedure, which is implemented with the help of information and communication technologies, aiming at achieving certain legal consequences and regulated by procedural legal norms and technical norms. The study also provides an analysis and evaluation of the effectiveness of the digital legal procedure, identifies the advantages of using electronic procedures in the period of crisis phenomena, such as facilitating access to justice, increasing the publicity and openness of the judicial process, and significantly reducing the time and material resources of the trial. At the same time, the possible risks of the digital transformation of court procedures in the context of the rule of law are outlined, which are associated with the violation of equal access to justice due to the lack of technical capabilities, ensuring confidentiality, the possibility of using discriminatory algorithms, the lack of procedural opportunities to appeal decisions made by artificial intelligence systems. Thus, the author proposed to develop a holistic concept of electronic court procedures, to establish digital procedural principles and rights of the subjects of such procedures at the regulatory level.

Встановлено відповідність електронних процедур вимогам верховенства права, що на сьогодні є основним критерієм легітимності діяльності органів державної влади. Методологічну основу наукової роботи склали загальнонаукові та спеціально-юридичні методи, зокрема системний, аналізу та синтезу, формально-юридичний, порівняльно-правовий. З'ясовано основні підходи до розуміння категорії юридичної процедури, запропоновано критерії класифікації залежно від наявності зв'язку з юридичним процесом на процесуальні та позапроцесуальні. Досліджено особливості вдосконалення процедур у сфері правозастосування, зокрема судочинства, під впливом цифрової трансформації. Сформульовано поняття електронної юридичної процедури як особливого виду, який реалізується за допомогою інформаційно-комунікаційних технологій, спрямований на досягнення певних правових наслідків і регламентований процедурними правовими нормами та технічними нормами. Наведено аналіз та оцінку ефективності цифрової юридичної процедури, визначено переваги використання електронних процедур у період кризових явищ, такі як полегшення доступу до правосуддя, підвищення публічності та відкритості судового процесу та значне скорочення часу і матеріальних ресурсів судового розгляду. Окреслено можливі ризики цифрової трансформації судових процедур у контексті верховенства права, що пов'язані з порушенням рівноправного доступу до правосуддя через відсутність технічних можливостей, забезпечення конфіденційності, можливістю використання дискримінаційних алгоритмів, відсутності процедурних можливостей оскарження рішень, прийнятих системами штучного інтелекту. Запропоновано розробити цілісну концепцію електронних судових процедур, на нормативному рівні закріпити цифрові процесу[1]альні принципи та права суб'єктів таких процедур.
ВЕРХОВЕНСТВО ПРАВА ТА ЕЛЕКТРОННА ЮРИДИЧНА ПРОЦЕДУРА: АНАЛІЗ СПІВВІДНОШЕННЯ
Keywords: електронна юридична процедура; цифрове судочинство; цифрова трансформація; верховенство права; electronic legal procedure; digital justice; digital transformation; rule of law